Determinants of Going Concern Audit Opinion on Manufacturing Companies Listed on the Indonesia Stock Exchange - Maya Sari; Aulia Febriana Sukma Batin (Journal of International Conference Proceedings (JICP), 2022)
The going concern audit opinion shows the auditor's doubts about the business continuity of the company. This study aims to analyze the effect of financial condition, company size, company growth, auditor client tenure and previous year's audit opinion on the acceptance of going concern audit opinion. This research is a type of associative quantitative research. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange as many as 162 companies and using purposive sampling technique in determining a sample of 108 manufacturing companies. The data collection technique used is the documentation technique and the data analysis technique used by SPSS windows version 23 software. The results show that simultaneously, the variables of financial condition, company size, company growth, auditor client tenure and previous year's audit opinion affect the acceptance of audit opinions. going concern. However, partially the company growth variable and auditor client tenure have no effect on the going concern audit opinion acceptance, while the financial condition variable, company size and the previous year's audit opinion affect the going concern audit opinion acceptance.Keywords: Financial Condition, Company Size, Company Growth, Auditor Client Tenure, Previous Year's Audit Opinion, Going Concern Audit Opinion.